Altered Neuronal Firing Pattern of the Basal Ganglia Nucleus Plays a Role in Levodopa-Induced Dyskinesia in Patients with Parkinson’s Disease - Li, Xiaoyu; Zhuang, Ping; Li, Yongjie (Frontiers in Human Neuroscience, 2015)
Background: Levodopa therapy alleviates the symptoms of Parkinson's disease (PD), but long-term treatment often leads to motor complications such as levodopa-induced dyskinesia (LID). Aim: To explore the neuronal activity in the basal ganglia nuclei in patients with PD and LID. Methods: Thirty patients with idiopathic PD (age, 55.1±11.0 years; disease duration, 8.7±5.6 years) were enrolled between August 2006 and August 2013 at the Xuanwu Hospital, Capital Medical University, China. Their Hoehn and Yahr scores ranged from 2 to 4 and their UPDRS III scores were 28.5±5.2. Fifteen of them had severe LID (UPDRS IV scores of 6.7±1.6). Microelectrode recording was performed in the globus pallidus internus (GPi) and subthalamic nucleus (STN) during pallidotomy (n=12) or STN deep brain stimulation (DBS; bilateral, n=12; unilateral, n=6). The firing patterns and frequencies of various cell types were analyzed by assessing single cell interspike intervals (ISIs) and the corresponding coefficient of variation (CV). Results: A total of 295 neurons were identified from the GPi (n=12) and STN (n=18). These included 26 (8.8%) highly grouped discharge, 30 (10.2%) low frequency firing, 78 (26.4%) rapid tonic discharge, 103 (34.9%) irregular activity, and 58 (19.7%) tremor-related activity. There were significant differences between the two groups (P<0.05) for neurons with irregular firing, highly irregular cluster-like firing, and low-frequency firing. Conclusion: Altered neuronal activity was observed in the basal ganglia nucleus of GPi and STN, and may play important roles in the pathophysiology of PD and LID.